Mad of Covid-19 / Anis Syazwani Salim - Salim, Anis Syazwani (Faculty of Art and Design, 2021)
Dealing with the unforeseen challenges caused by the COVID-19 pandemic has taken a significant toll on people all across the world. The spread of the pandemic outbreak does not only severely impact our health, but continues to paralyze the global economy. Deeply impacted by our current situation and touched by efforts of government and frontliners to end the crisis, I was inspired to create an artwork entitled , "Mad of Covid-19". In my artwork, I have highlighted two main characters which are a man and an image representing the virus. As the novel virus keeps spreading, healthcare professionals across the globe are faced with an unprecedented situation of having to make difficult decisions and work under extreme pressures. I have also expressed the importance of the man as the frontliner having to wear protective clothing, helmets, goggles, or other garments or equipment designed to protect from infections. This could help raise more awareness to remind people to wear a face mask which can help prevent the spread of the virus. Face masks are part of an infection control strategy to eliminate cross-contamination.